2015
DOI: 10.1111/1346-8138.13200
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of docetaxel as first‐line chemotherapy for metastatic extramammary Paget's disease

Abstract: In invasive extramammary Paget's disease (EMPD), distant metastases may develop and the condition may become fatal; however, no standardized treatment has been established. Although based on only a few cases, several chemotherapy regimens were reported to be promising. We conducted a multicenter, retrospective study to evaluate the efficacy of docetaxel for metastatic EMPD. We retrospectively collected data on 18 metastatic EMPD patients treated using docetaxel from 1998 to 2012 in 12 institutes in Japan. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 21 publications
2
66
0
Order By: Relevance
“…Thus, DTX monotherapy is the preferred first‐line treatment based on its lower toxicity and the certain tumor shrinkage effect (RR of 58%). However, its efficacy is not durable, and the reported median PFS and OS were 7.1 and 16.6 months, respectively . Of our five patients receiving PET, four patients showed PR.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, DTX monotherapy is the preferred first‐line treatment based on its lower toxicity and the certain tumor shrinkage effect (RR of 58%). However, its efficacy is not durable, and the reported median PFS and OS were 7.1 and 16.6 months, respectively . Of our five patients receiving PET, four patients showed PR.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, patients undergoing treatment with these combination chemotherapies usually suffer from severe side‐effects and require repeated hospitalization. Thus, DTX monotherapy has been highlighted recently for the first‐line treatment of metastatic EMPD, based on its decent efficacy with few side‐effects . The efficacy of DTX monotherapy has been demonstrated with two different administration schedules in various cancer types: a triweekly regimen involving i.v.…”
Section: Introductionmentioning
confidence: 99%
“…While a triweekly regimen is officially recommended for DTX, various clinical trials have reported similar pharmacokinetics, similar efficacy and less toxicity with a weekly regimen . To date, two retrospective studies have evaluated the feasibility and efficacy of DTX at 60 mg/m 2 per 3/4 weeks per infusion as first‐line therapy for metastatic EMPD . However, the treatment outcome of its weekly regimen for metastatic EMPD has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Because EMPD is a rare cutaneous carcinoma, effective treatments of advanced cases have not been fully established. Yoshino et al . reported that the response rate of DOC was 58% in a 12‐case study.…”
Section: Discussionmentioning
confidence: 98%